Do Existing MRI Definitions of Knee Osteoarthritis Identify Knees That Will Develop Clinically Significant Disease Over Up To 11 Years of Follow-Up? - Chang, Alison H.; Roemer, Frank; Guermazi, Ali; Almagor, Orit; Lee, Jungwha; Chmiel, Joan S.; Muhammad, Lutfiyya N.; Song, Jing; Sharma, Leena (Arthritis and Rheumatology, 2024)
Objective: In individuals without radiographic knee osteoarthritis (OA), we investigated whether magnetic resonance imaging (MRI)–defined knee OA at baseline was associated with incident radiographic and symptomatic disease during up to 11 years of follow-up. Methods: Osteoarthritis Initiative participants without tibiofemoral radiographic knee OA at baseline were assessed for MRI-based tibiofemoral cartilage damage, osteophyte presence, bone marrow lesions, and meniscal damage/extrusion. We defined MRI knee OA using alternative, reported definitions (Def A and Def B). Kellgren–Lawrence (KL) grade, joint space narrowing (JSN), and frequent knee symptoms (Sx) were assessed at baseline, 1-, 2-, 3-, 4-, 6-, 8-, and 10/11-year follow-up visits. Incident tibiofemoral radiographic knee OA (outcome) was defined as (1) KL ≥2, (2) KL ≥2 and JSN, or (3) KL ≥2 and Sx. Adjusted Cox proportional hazards regression models examined associations of baseline MRI-defined knee OA (Def A and Def B) with incident outcomes during up to 11 years of follow-up. Results: Among 1,621 participants (mean age ± SD 58.8 ± 9.0 years, mean body mass index ± SD 27.2 ± 4.5 kg/m2, 59.5% women), 17% had MRI-defined knee OA by Def A and 24% by Def B. Baseline MRI-defined knee OA was associated with incident KL ≥2 (odds ratio 2.94 [95% confidence interval (95% CI) 2.34–3.68] for Def A and 2.44 [95% CI 1.97–3.03] for Def B). However, a substantial proportion of individuals with baseline MRI-defined knee OA did not develop incident KL ≥2 during follow-up (59% for Def A and 64% for Def B). Findings were similar for the other two outcomes. Conclusion: Current MRI definitions of knee OA do not adequately identify knees that will develop radiographic and symptomatic disease.
CRIS-Team Scopus Importer:2024-11-01